SYNTHESIS DIBENZIL IS REGISTERED THROUGH THE POLYMERIZED POLYMERYLENE AS ALTERNATIVE RECYCLE PLASTIC RECYCLE - Suwardi, Suwardi; Partana, Crys Fajar; Salim, Agus (Jurnal Penelitian Saintek, 2005)
Synthesis dibenzyl terephathalate were done through PET softdrinkbottles degradation by refluxing in benzyl alcohol at 14 C temperature for 20, 24. and 28 hours in the presence of zinc acetate catalyst. The result of degradation was purified by recristalization in methanol and then melting point (mp), FTIR, I H NMR spectra, and TLC spot were determined. The melting point of product degradation.for 28 hours was 98-99 "c. Based FTIR spectra known thatcompounds of product degradation have OH, C=O, C-O, CH,monosubstituted benzene, disubstituted benzene groups, while on IH NMR spectra showed chemical shift at 8.2 ppm (s, IO H of monosubtituted benzene), 7.5 ppm (s, 9 H consist of 4 H disubstituted benzene and 5 H of aromatic benzyl alcohol), 5.4 ppm (s, 1 H from OH benzyl alcohol), 4.8 ppm (s, 4 H of methylene), and 2.9 ppm (s. 7H of other traces). The single spot ofTLC plate indicated that productdegradation for 28 hours might be a single compound. Based these characterization concluded that compound of product degradation was dibenzyl terephthalate contains benzyl alcohol and other traces.